(untitled) (Лучшие интеллектуальные исследования, 2025)
Abstract: the article describes the use of new pedagogical technologies in teaching and improving the quality. The reasons for the emergence of new psychological and pedagogical technologies are the need for a deeper consideration and use of the psychophysiological and personal characteristics of students.